DOA DALAM AL-QUR’AN - Firdaus Firdaus; Amir Hamzah; Siar Ni'mah (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2023)
Prayer is a daily practice that is intended as a form of solemn communication to the Lord. In praying, a Muslim has been given guidance in the Qur'an. This study discusses the intended prayer and how the actual meaning is related. This research was conducted to reveal what kinds of actions are contained in the Al-Qur'an and how the interpretation of mufasir interprets them. The research method used is literature with a thematic interpretation approach. The results found several explanations related to the meaning of the prayer itself, such as the importance of praying, the conditions that must be met for the prayer to be granted, and what the types of prayer are like in the Qur'an. This is so that it becomes a common reference in the process of human closeness to the Almighty, the answerer of prayer.